2018
DOI: 10.21873/invivo.11232
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of β-Carotene, Lycopene and Tri-n-butylborane, a Scavenger of Reactive Oxygen Species

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 35 publications
(36 reference statements)
1
45
0
1
Order By: Relevance
“…Since insulin resistance and type 2 diabetes are conditions closely related with inflammation and studies already showed that tomato-oleoresin ameliorates the inflammation, this property may explain the beneficial effect on glucose metabolism [41]. The antioxidant and anti-inflammatory effect of lycopene can also be explained by considering its well-established ability, through electrophilic metabolites, to activate Nrf2 pathway thus inducing phase II detoxifying/antioxidant enzymes and inhibiting NF-κB activation [42,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Since insulin resistance and type 2 diabetes are conditions closely related with inflammation and studies already showed that tomato-oleoresin ameliorates the inflammation, this property may explain the beneficial effect on glucose metabolism [41]. The antioxidant and anti-inflammatory effect of lycopene can also be explained by considering its well-established ability, through electrophilic metabolites, to activate Nrf2 pathway thus inducing phase II detoxifying/antioxidant enzymes and inhibiting NF-κB activation [42,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Lycopene is a carotenoid without provitamin A activity, which gives red colors to vegetables such as tomatoes, red grapefruit, watermelon, and apricots [19]. This carotenoid is a powerful antioxidant with anti-inflammatory activity [20], which has been shown to modulate important metabolic processes in the body, attenuating complications of obesity and restoring liver function. The lycopene is a liposoluble molecule, which depends on dietary lipids to be absorbed.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular and molecular studies have revealed lycopene, which not only inhibits lipid peroxidation but also quenches ROS, 24 to be one of the strongest antioxidants. 25 It has been commonly used as an antioxidant agent in traditional medicine and has been reported to have protective effects for the treatment of cardiovascular diseases, neurotoxicity, hepatic injury, and nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%